Konsep, Fungsi, Dan Aplikasi Manajemen Sumber Daya Manusia Secara Efektif Dan Efisien Untuk Mencapai Tujuan Organisasi - Samsudin, Acep; Brian, Johannes Baptista; Amanda, Riska; Putri, Valiza Eka; Dec’caprio, Yoghananda (Jurnal Ilmiah Wahana Pendidikan, 2024)
Human Resource Management (HRM) plays a central role in achieving organizational goals effectively and efficiently. This abstract discusses HR concepts, functions, and applications with a focus on its role in supporting organizational goals. The concept of HRM involves the strategic alignment of an organization's workforce with its mission and vision. HRM functions include recruitment, selection, training, performance evaluation and employee development. HR practice applications include creating a supportive work environment, enhancing employee engagement, and promoting diversity and inclusion. Effective and efficient utilization of HRM principles contributes to increased productivity, employee satisfaction, and ultimately organizational success. The purpose of this research is to study the concepts, functions, and applications of HRM. Human resource management is the planning, implementation, and administration of human resources effectively and efficiently to achieve the goals of an organization. As one of the resources of an organization, human resources have a very important role in achieving organizational goals..